Creep Investigation on Shale-Like Material with Preexisting Fissure under Coupling Temperatures and Confining Pressures - Yongyan Wang; Hongwei Wang; Xiao Shi (Advances in Civil Engineering)
In order to investigate the influence of temperature, confining pressure, and preexisting fissure on creep characteristics of rock mass, multistage creep experiments were performed on shale-like material, with preexisting fissure under different temperatures and confining pressures. The results showed that new microcracks generated and propagated with the increase of temperature in both uniaxial and triaxial creep experiments, and the generation and propagation were most pronounced at 60°C and least at 20∼50°C in uniaxial creep experiments. The generation and propagation were restricted by confining pressure. Temperature had less influence on the creep strain rate in triaxial creep experiment, whereas it had a significant influence on the steady-state creep rate in uniaxial creep experiment. The influence of confining pressure on the steady-state creep rate was slight when confining pressure was 1 MPa, whereas it was obvious when confining pressure was 3∼7 MPa. The closure of preexisting fissure promoted the creep strain rate, and the closure was incomplete when confining pressure was below 3 MPa, whereas it was complete when confining pressure at 5 and 7 MPa.